2001
DOI: 10.1007/s004410000313
|View full text |Cite
|
Sign up to set email alerts
|

Double immunocytochemistry of vasoactive intestinal peptide and cGnRH-I in male quail: photoperiodic effects

Abstract: Reproduction in Japanese quail is primarily regulated by photoperiod. Vasoactive intestinal peptide (VIP) has been suggested as a transducer of environmental information, especially photoperiodic cues, to the hypothalamo-pituitary-gonadal axis. To investigate the possible interaction of VIP and the reproductive (gonadotropin-releasing hormone, GnRH) system, double-immunocytochemical staining for VIP and cGnRH-I was conducted in sexually mature male quail held under a long-day photoperiod (16L:8D; LD) and in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…The distribution of GnRH-ir neurons described for the septum closely matches the position of our LSc.vl, LSc.l, and CcS. This topographical assignment is corroborated by double-label data showing a close correspondence between GnRH-ir neurons and fibers immunoreactive for VIP and CRF (Teruyama and Beck, 2001;Wang and Millam, 1999). The CRF double-label data are particularly informative, as CRF-ir fibers in the present study were located only to the LSc.vl, LSc.l, and CcS.…”
Section: Histochemical Comparisons With the Major Septal Divisions Ofsupporting
confidence: 79%
“…The distribution of GnRH-ir neurons described for the septum closely matches the position of our LSc.vl, LSc.l, and CcS. This topographical assignment is corroborated by double-label data showing a close correspondence between GnRH-ir neurons and fibers immunoreactive for VIP and CRF (Teruyama and Beck, 2001;Wang and Millam, 1999). The CRF double-label data are particularly informative, as CRF-ir fibers in the present study were located only to the LSc.vl, LSc.l, and CcS.…”
Section: Histochemical Comparisons With the Major Septal Divisions Ofsupporting
confidence: 79%
“…The present study has revealed an identical distribution in the hypothalamus and optic tectum to that reported for VIP mRNA in the chicken (Kuenzel et al 1997), and for VIP-like-immunoreactive neuronal cell bodies in the quail brain (Aste et al 1995;Teruyama and Beck 2001). VIP mRNA was detected in hypothalamic structures implicated in the regulation of food intake, including the lateral hypothalamic area extending into the PVN, and the IN.…”
Section: Discussionsupporting
confidence: 64%
“…Brains were returned to the same fixative overnight and then transferred to a sucrose solution (30% in 0.1 M sodium phosphate buffer) at 4掳C. Fixed brains were placed in a brass mold with 2-mm slots and blocked at A 8.8 and A 0.6 (Kuenzel and Masson, 1988) to obtain the hypothalamic areas identified by Teruyama and Beck (2001) as containing high numbers of VIP-ir cells in sexually mature quails. Blocks were sectioned at 50 碌m using a freezing microtome and sections were collected in 0.01 M PBS, pH 7.4.…”
Section: Blood Sampling and Brainmentioning
confidence: 99%